The N‐acetylglucosamine catabolic gene cluster in Trichoderma reesei is controlled by the Ndt80‐like transcription factor RON1 - Kappel, Lisa (Mol Microbiol, 2015)
Chitin is an important structural constituent of fungal cell walls composed of N‐acetylglucosamine (GlcNAc) monosaccharides, but catabolism of GlcNAc has not been studied in filamentous fungi so far. In the yeast C andida albicans, the genes encoding the three enzymes responsible for stepwise conversion of GlcNAc to fructose‐6‐phosphate are clustered. In this work, we analysed GlcNAc catabolism in ascomycete filamentous fungi and found that the respective genes are also clustered in these fungi. In contrast to C . albicans, the cluster often contains a gene for an Ndt80‐like transcription factor, which we named RON1 (regulator of N‐acetylglucosamine catabolism 1). Further, a gene for a glycoside hydrolase 3 protein related to bacterial N‐acetylglucosaminidases can be found in the GlcNAc gene cluster in filamentous fungi. Functional analysis in T richoderma reesei showed that the transcription factor RON1 is a key activator of the GlcNAc gene cluster and essential for GlcNAc catabolism. Furthermore, we present an evolutionary analysis of Ndt80‐like proteins in Ascomycota. All GlcNAc cluster genes, as well as the GlcNAc transporter gene ngt1, and an additional transcriptional regulator gene, csp2, encoding the homolog of N eurospora crassa  CSP2/GRHL, were functionally characterised by gene expression analysis and phenotypic characterisation of knockout strains in T . reesei.